Implementation of Single Minutes of Exchange Die (SMED) in Malaysia Metal Stamping Industry: A Case Study - Muhamad Arifpin, Mansor; A. R., Ismail; M. R. M., Yasin; A., Halim (2015)
Downtime loss due to long set-up time will lead to shorter actual production time. This situation will result in a loss to the company because they could not produce their products as planned. Therefore, set-up time needs to be reduced to maximize the resources invested by the company. The most popular approach to is an approach to improve setup time is Single Minutes of Exchange Die (SMED), developed by Shigeo Shingo in early 1960s. Setup operations were divided by into fundamental types; Internal setup and External setup. By Converting Internal setup to External setup, the company can reduced the setup time and thus, lead to longer actual production time. This paper presents an afford of a Malaysia’s metal stamping company in implementing SMED in their company. The company is a supplier of passenger car’s components to Malaysia’s major car makers. The implementation was carried out by separating Internal and External Setup, converting Internal to External Setup and finally streamlining all aspects of the setup operation. After implemented SMED approach, the company managed to reduce their set-up time from 32 minutes to 12 minutes. However, the company still working hard to achieve the objective of SMED, which is to complete all changeovers are in a single number of minutes or less than 10 minutes.